2014
DOI: 10.1055/s-0034-1395531
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Improves Fatty Liver Independently of Insulin Sensitization and Appetite Suppression in Hepatocyte-Specific Pten-Deficient Mice with Insulin Hypersensitivity

Abstract: Nonalcoholic fatty liver disease (NAFLD) is recognized as the hepatic component of the metabolic syndrome. Although NAFLD is a major cause of cirrhosis and cancer of the liver of unknown cause, no established pharmacological treatment for NAFLD has been established yet. It has been reported that leptin treatment improved fatty liver dramatically as well as insulin resistance and hyperphagia in patients with lipodystrophy. However, it is unclear whether leptin improves fatty liver independently of these metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…However, incomplete β-oxidation leads to the re-esterification of fatty acids into TG, which is one of the important causes of TG accumulation in the liver. Yamamoto-Kataoka et al (2015) reported that the liver-specific deletion of PTEN in mice enhanced TG accumulation in the liver. Interestingly, we found that PTEN knockdown significantly increased the TG content in calf hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, incomplete β-oxidation leads to the re-esterification of fatty acids into TG, which is one of the important causes of TG accumulation in the liver. Yamamoto-Kataoka et al (2015) reported that the liver-specific deletion of PTEN in mice enhanced TG accumulation in the liver. Interestingly, we found that PTEN knockdown significantly increased the TG content in calf hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…83,84 Animal trials, human trials, and reviews seem to support the application of leptin or its efficacy in obesity or NAFLD considering its beneficial effect on IR and liver fat accumulation. 8590 However, Imajo and colleagues 91 reported that obesity-induced leptin plays a crucial role in NASH progression via enhanced responsivity to endotoxin, and Polyzos and colleagues 92 concluded that a high circulating leptin level was associated with severity of NAFLD. Above all, the effect of leptin on NAFLD still needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that dietary soy proteins suppress HFHS diet-induced leptin resistance. Although further analysis is needed regarding the relation between leptin resistance and fatty liver (50), it has been demonstrated that serum leptin levels are elevated in patients with fatty liver, independently of the body-mass index and percentage of body fat (51), and leptin improves fatty liver by stimulation of b-oxidation (52). It was reported that leptin suppressed the lipogenic enzyme gene by down-regulating the SREBP1c gene (53), suggesting that in the HFHS-b-conglycinin group the lower leptin resistance was associated with lower expression levels of FAS and ChREBP, which was regulated by SREBP1c.…”
Section: Discussionmentioning
confidence: 99%